A case of brucella spondylodiscitis with extended, multiple-level involvement - Ozden, M; Demirdiag, K; Kalkan, A; Ozdemir, H; Yuee, P (Lippincott Williams & Wilkins, 2005)
Brucellosis is a zoonosis that affects several organs and has a protean presentation. The authors report the case of a 61-year-old mate patient with brucellar spondylodiscitis involving several vertebrae and a paravertebral abscess localized in the erector spinae muscle. Diagnosis was made by positive blood culture and MRI. No relapse was seen with a combined treatment (doxycycline/rifampin) for 3 months, followed by doxycycline alone for 6 months. Almost all radiologic findings disappeared at the end of a 1-year follow-up without any further treatment.
Keywords: brucella; multiple-level involvement; paravertebral abscess; spondylodiscitis